Qualitative Methods in Media Entrepreneurship Research: Clarification of the terms Framework, Model and Pattern (2019)
Interchangeable use of some terms that imply on different concepts and constructs has been a challenge for the students and novice researchers. In particular, terms such as framework, model, pattern and the verbs such as design, identify, present, propose have been used in several cases in the different meaning and cause confusion for the researchers. This paper is a conceptual article that clarifies the use of such technical terms in qualitative researches in the area of media entrepreneurship. Simply, it defines framework as the limit and boundaries of a never studied phenomenon that includes factors and elements; model as a depiction of relationship among the factors and elements that predicts how the phenomenon works, and pattern as a previously successfully examined model that can be benchmarked by the future researchers. Then the proper verbs for these technical terms have been suggested. The findings are applicable in the media entrepreneurship and similar areas of qualitative researches, including creative industries.